Impact of spiritual meditation on drug addiction recovery and wellbeing: a systematic review - Rohayah, Husain (2020)
It is well recognized throughout the history that religiosity, spirituality and the meditation practice have significant effects to the physical and mental health. Hence, this paper interested to evaluate the effectiveness of spiritual meditation on drug addiction recovery and its effects on psychological and mental health aspects. Three main databases in medicinal and psychology field were screened to identify the eligible studies which are PubMed, Cochrane and Scopus by using Boolean expression. Fourteen papers were included in this review. Standardized mean differences were calculated based on the intergroup mean difference and standard deviation followed by Cochran’s Q and I2 determination for heterogeneity analysis. The mean differences were statistically pooled in the meta-analysis and presented as a forest plot. The risk of bias was high for each study and assessed using the Jadad scale. The meta-analysis showed significant differences in across studies for addiction related outcome (I2 =27%, 95% CI: -1.703, -0.454), anxiety (I2 =0%, 95% CI: -0.874, -0.634) and stress (I2 =100%, 95% CI: -0.874, -0.634). In general, spiritual meditation may promote the addiction recovery as well as improve the psychological and mental health outcomes by reducing the depression, anxiety and stress symptoms. In conclusion, randomized control trial on spiritual meditation gave positive impact on the addiction behavior as well as mental health and clarifies its reliability on addiction therapy problems.